P26 Utility of the chest X-ray in the era of IGRA testing for latent TB prior to anti-TNF therapy. (14th November 2013) - Tsim, S; Anwar, J; McLure, L; Roditi, G; Cotton, MM
Abstract : Introduction: Anti-TNF therapies are associated with increased risk of reactivation of latent Mycobacterium tuberculosis infection (LTBI). Screening for LTBI is recommended prior to commencing anti-TNF therapy. BTS guidelines for screening incorporate epidemiologic risk, clinical examination, Mantoux testing and chest radiography (CXR). Other guidelines recommend use of interferon gamma release assays (IGRAs). We audited the use of IGRA and CXR as part of screening for LTBI in patients who were being considered for immuno-suppresant therapy. Methods: All IGRAs requested from Glasgow Royal Infirmary (GRI) over a 21 month period were retrospectively assessed for the following: patient history, test indication and result, CXR report and patient outcome. GRI serves the most deprived population in the UK. A single laboratory provides TB bacteriology for the whole of Glasgow, and is the sole provider of IGRA testing for LTBI utilising the 'T-Spot. TB '. Results: Between August 2010-May 2012, 354 T-Spot. TB tests were performed. Planned immuno-suppressant therapy was the indication in 70% (n = 248); etanercept was the most commonly proposed drug (32%, n = 78), followed by adaluminab (29%, n = 72), anti-TNF not otherwise specified (11%, n = 28) and infliximab (6%, n = 15). Of those for whom immunosupression was the indication, 80% (n = 199) of T-Spot. TB tests were negative, 17% (n = 41) indeterminate and 3% (n = 8) positive. A CXR was performed in all but 6% (n = 11). CXR findings and patient outcomes for patients with negative T-Spot. TB tests are summarised in table 1. All 16 abnormal CXRs were referred to a TB specialist for review and none had chemoprophylaxis commenced or any alterations in their management recommended. Conclusions: With increasing use of IGRAs, new guidance on screening for LTBI prior to anti-TNF therapy is required. In our cohort of 248 patients, the majority had a negative T-spot test reflecting that despite high levels of deprivation TB prevalence in Glasgow is low. CXR did not alter patient management, TB chemoprophylaxis was not given in any case and there were no cases of LTBI reactivation or de novo TB within the follow-up period (11–32 months). We propose that if IGRA is negative, CXR is not required as part of screening for LTBI prior to anti-TNF therapy.